2017
DOI: 10.1186/s13717-017-0100-x
|View full text |Cite
|
Sign up to set email alerts
|

Are Northeastern U.S. forests vulnerable to extreme drought?

Abstract: In the Northeastern U.S., drought is expected to increase in frequency over the next century, and therefore, the responses of trees to drought are important to understand. There is recent debate about whether land-use change or moisture availability is the primary driver of changes in forest species composition in this region. Some argue that fire suppression from the early twentieth century to present has resulted in an increase in shade-tolerant and pyrophobic tree species that are drought intolerant, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 116 publications
(147 reference statements)
0
10
0
Order By: Relevance
“…Even though the xeric site is chronically exposed to lower soil moisture conditions, we found that understory NDVI was significantly lower for all levels of PDSI compared to the mesic site, showing that understory species were not able to thrive at the level of that of the mesic site under drought conditions. However, the magnitude of NDVI change (i.e., slope of the regression) was lower at the xeric site when severity of drought increased, indicating that plant functional types at the site could buffer drought conditions more effectively (Coble et al 2017, Granda et al 2018, such that understory NDVI decreased by half as much as at the mesic site. In addition, overall ecosystem productivity at xeric sites was shown to recover more rapidly from drought (Starr et al 2016), compared to more mesic sites, which was the result of drought-resistant plant species in the over-and understory (Wright et al 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Even though the xeric site is chronically exposed to lower soil moisture conditions, we found that understory NDVI was significantly lower for all levels of PDSI compared to the mesic site, showing that understory species were not able to thrive at the level of that of the mesic site under drought conditions. However, the magnitude of NDVI change (i.e., slope of the regression) was lower at the xeric site when severity of drought increased, indicating that plant functional types at the site could buffer drought conditions more effectively (Coble et al 2017, Granda et al 2018, such that understory NDVI decreased by half as much as at the mesic site. In addition, overall ecosystem productivity at xeric sites was shown to recover more rapidly from drought (Starr et al 2016), compared to more mesic sites, which was the result of drought-resistant plant species in the over-and understory (Wright et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…However, the magnitude of NDVI change (i.e., slope of the regression) was lower at the xeric site when severity of drought increased, indicating that plant functional types at the site could buffer drought conditions more effectively (Coble et al. , Granda et al. ), such that understory NDVI decreased by half as much as at the mesic site.…”
Section: Discussionmentioning
confidence: 99%
“…It has relatively narrow xylem conduits (i.e., diffuseporous xylem; Ellmore et al 2006) and has been shown to exhibit isohydric stomatal behavior in response to drought [24]. In contrast, Q. rubra is moderately shade-tolerant [60] and moderately drought-tolerant [59]. Trees of this species have large xylem conduits (i.e., ring-porous xylem; Ellmore et al 2006) and exhibit anisohydric stomatal behavior in response to drought [8].…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the theoretical framework outlined in by Martinez‐Vilalta, Poyatos, Aguade, Retana and Mencuccini (2014), we calculated the slope of the linear line for each of the treatments for normal year conditions (2015) and ENSO conditions (2016). The slopes (σ) of the lines loosely represent isohydric and anisohydric behaviour (Coble et al, 2017; Martinez‐Vilalta et al, 2014). In this framework, four distinct behaviours exist: strict isohydric (σ = 0), partial isohydric (0 < σ < 1), strict anisohydric (σ = 1) and extreme anisohydric (σ > 1).…”
Section: Methodsmentioning
confidence: 99%